QoS simulation and analysis of HTTP over LEO satellite constellation - Audah, Lukman; Sun, Zhili; Cruickshank, Haitham (2012)
In this paper, we present an end-to-end QoS simulation studies on internetworking of remote LAN and long range communications over LEO-Iridium satellites constellation taking SuperJARING network in Malaysia as an example. A macro level network simulation scenario based on actual network topology in Malaysia is implemented as Diffserv network model using the network simulator-2 (NS-2). Web traffic (HTTP) is used as the internet traffic models in the simulation analysis. All simulations are carried out in error-free and link-loss environment. In error-free simulations, the accumulative network traffic loads are varied from 20%, 50% and 80% while in linkloss environment simulations only 20% traffic load is used with bit error rate (BER) varied from 1x10-5 , 1x10-4 and 2x10-4 . We compare the empirical TCP throughput traces with analytical model for validation. The results show clearly that QoS can be achieved with IP Diffserv over satellites constellation like Iridium.